DNA Hypomethylation of DOCK1 Leading to High Expression Correlates with Neurologic Deterioration and Poor Function Outcomes after Spontaneous Intracerebral Hemorrhage. (27th September 2021) - Gao, Yufeng; Fu, Xiaojie; Yu, Lie; Zhang, Di; Lu, Zhengfang; Cui, Kefei; Liu, Chang; Man, Jiang; Wang, Jianping
Abstract : Objective . Spontaneous intracerebral hemorrhage (ICH) is a blood clot arising in the brain parenchyma in the absence of trauma or surgery and accounts for 10% to 15% of all strokes, leading to higher rates of mortality and morbidity than either ischemic stroke or subarachnoid hemorrhage. We sought to investigate the potential association of DOCK1 with neurological deficits and outcomes in patients with spontaneous ICH. Methods . Identification of methylation-regulated differentially expressed genes (MeDEGs) between ICH patients and matched controls was performed by analyzing the raw data from the GSE179759 and GSE125512 datasets deposited in the Gene Expression Omnibus. A total of 114 patients who were admitted to our hospital for spontaneous ICH were retrospectively analyzed, with 108 healthy volunteers who had received physical examinations at the same period as controls. The mRNA expression of DOCK1 was determined by quantitative real-time polymerase chain reaction (qRT-PCR). The hematoma volume was calculated according to the Coniglobus formula. The severity of neurological deficits was evaluated using National Institutes of Health Stroke Scale (NIHSS) scores and function outcomes were evaluated by modified Rankin Scale (mRS) scores. Results . A total of 15 MeDEGs between ICH patients and matched controls were identified. The mRNA expression of DOCK1 was remarkably higher in the serum samples of patients with spontaneous ICH than in the healthy controls. According to hematoma volume after ICH attack, small (<10 mL), medium (10 to 30 mL), and large (>30 mL) groups were arranged. The proportions of male patients and patients aged ≥60 years were significantly higher in the large group than in the small and medium groups (P < 0.05 ). The mRNA expression of DOCK1 was significantly higher in the large group than in the small and medium groups (P < 0.05 ). According to NIHSS scores, mild (NIHSS scores ≤15), moderate (NIHSS scores from 16 to 30), and severe (NIHSS scores from 31 to 45) groups were classified. It was observed that the severe group had higher proportions of male patients and patients aged ≥60 years than the mild and moderate groups (P < 0.05 ). The severe group exhibited a higher mRNA expression of DOCK1 than the mild and moderate groups (P < 0.05 ). According to mRS scores, higher proportions of male patients and patients aged ≥60 years were observed in the unfavorable group than the favorable group (P < 0.05 ). The patients in the unfavorable group showed an elevated DOCK1 mRNA expression compared to those in the favorable group (P < 0.05 ). Conclusion . The study provided evidence that male gender, older age, and higher DOCK1 mRNA expression were related to higher admission hematoma volume, neurologic deterioration, and poor function outcomes in patients with spontaneous ICH.